Safety of live attenuated herpes zoster vaccine in adults 70–79 years: A self-controlled case series analysis using primary care data from Australia's MedicineInsight program. Issue 23 (13th May 2020) - Totterdell, James; Phillips, Anastasia; Glover, Catherine; Chidwick, Kendal; Marsh, Julie; Snelling, Tom; Macartney, Kristine
Highlights: Application of self-controlled case series design in Australian primary care setting. Use of novel primary care data source (MedicineInsight) for vaccine safety. No new safety concerns identified for live attenuated herpes zoster vaccine. Expected increased risk of injection site reaction supports the methodology. No increased risk of myocardial infarction or stroke following vaccination. Abstract: Background: Australia introduced a funded shingles vaccination program for older adults in November 2016, administered predominantly in primary care clinics. MedicineInsight, a nationally representative primary care database, was used to investigate the risk of pre-specified outcomes following live attenuated herpes zoster vaccine (ZVL) in Australia. Methods: Individuals aged 70–79 years who received ZVL between 1 November 2016 and 31 July 2018 were identified from MedicineInsight. The self-controlled case series (SCCS) method was used to estimate the seasonally-adjusted relative incidence (RI) of seven pre-specified outcome events (injection site reaction (ISR) [positive control], burn [negative control], myocardial infarction (MI), stroke, rash, rash with an antiviral prescription, and clinical attendance) during a plausible post-vaccination at-risk window compared with times distant from vaccination. Sensitivity analyses examined the effect of common concomitant vaccinations and restriction to first outcome events. Results: A total of 332, 988 vaccination encounters among 150, 054 individuals were identified during the study period; over 2 million clinical attendances were observed. There was an increased RI of ISR in the seven days following ZVL (RI = 77.4, 95% CI 48.1–124.6); the RI of clinical attendance (RI = 0.94, 95% CI 0.94–0.95) and stroke (RI = 0.58, 95% CI 0.44–0.78) were lower in the 42 days following administration of ZVL compared to control periods. There was no evidence of a change in the RI of MI (RI = 0.74, 95% CI 0.41–1.33), rash (RI = 0.97, 95% CI 0.88–1.08), or rash with antiviral prescription (RI = 0.83, 95% CI 0.62–1.10) in the 42 days following ZVL compared to control periods. Conclusion: No new safety concerns were identified for ZVL in this study based on a novel, Australian primary care data source. An expected increased risk of ISR was identified; findings in relation to cardiovascular disease were reassuring but require confirmation using additional data, including hospital records.